Evaluating Indonesian EFL Pre-Service Teachers’ ICT Proficiency in Technology-Integrated Lesson Planning - Dwiniasih; Ahmad Bukhori Muslim; Fazri Nur Yusuf; Siti Rojab Rodliyah; Isti Siti Saleha Gandana (Journal of Education Technology, 2026)
Significant gaps persist between prospective teachers’ perceived digital competencies and their actual professional teaching capabilities in technology-integrated English language education. This study evaluated the effectiveness of a triangulated assessment framework in identifying digital competency gaps among prospective English teachers and examined the alignment between self-perception, professional expectations, and demonstrated performance. A convergent parallel mixed-methods design was employed involving 50 prospective English teachers and 39 in-service teachers from West Java, Indonesia. Data were collected through DigComp 2.2-based self-assessment surveys, stakeholder expectation surveys, and performance-based evaluation of digital learning modules. Findings revealed that prospective teachers demonstrated low-intermediate proficiency across all DigComp domains (M=1.81–2.30). In-service teachers established consistently high expectations regarding digital teaching competencies, particularly responsive digital learning design (M=5.0). Performance-based evaluation identified critical weaknesses in accessibility compliance, interactive technology integration, and professional presentation standards despite adequate instructional content quality. Triangulated assessment further confirmed significant discrepancies between perceived competence and authentic digital teaching performance. Results indicate that current teacher preparation programs primarily develop foundational digital literacy while insufficiently addressing professional digital competencies required for effective technology-integrated instruction.